MAKING DENTAL AND ORAL CARE LITERACY DURING A PANDEMIC AS COMMUNITY SERVICE - Rini Devijanti Ridwan; Devi Rianti; Mahela Sefrian Luthfimaidah; Dimas Rudianto Fardha (Universitas Airlangga, 2022)
Coronavirus Disease-19 (COVID-19) has been spread fast so World Health Organization (WHO) declared COVID-19 as a pandemic. In Indonesia, data from the first patience until October 2021, this pandemic has infected more than four million Indonesians citizen, soon after government made policies for people to stay at home if there is no urgent need to leave the house. Transmission of COVID-19 which is through droplets and airborne causing contact from people to other should be limited if it is not necessary, as well as in conditions of fulfilling dental and oral care needs. The main transmission conditions through droplets like this cause health workers, especially the dentistry sector to be at high risk for infected by COVID-19, because dentists must have direct contact with the patients oral cavity who may also have become carriers of COVID-19, this can be done through direct contact with saliva, patient's blood and can also be caused by touch a tool or object which surfaces has been contaminated by this virus. Although it is recommended not to go to dentist for treatment, the Centers for Disease Control and Prevention (CDC) still give recommendations to patient to be treated for emergency cases. So education and literacy are needed to increase public knowledge about what cases included to an emergency cases, how to go or get treatment in dental and oral health needs during the pandemic, so that people can still get treatment if they are in a condition that is really needed.